New nonsteroidal anti-inflammatory drug in the treatment of different ocular pathology - A. J. Slonimskij; J. B. Slonimskij; A. S. Obrubov (Oftalʹmologiâ)
Purpose. Evaluation of efficacy and safety of a new nonsteroidal anti-inflammatory drug (NSAID) Broxinac (bromfenac 0.09 %).Patients and methods.The study included 79 patients with different mainly inflammatory eye pathology. All of them have got the instillation of Broxinac 1 per day. The duration of treatment ranged from 1 to 4 weeks.Results. No corneal complications and allergic reactions during the treatment were observed. Patients did not note any significant discomfort during instillation of Broxinac eye drops. In all cases fast relief of pain was noted. We registered not only quick decrease of exudative reaction in the anterior chamber, but also decrease of inflammation in posterior segment of the eye (fibrinous reaction in vitreous by uveitis).Conclusion. Broxinac (bromfenac 0.09 %) is new effective and safe ophthalmic NSAID. Broxinac is very convenient eye drops with instillation only once per day. It should be used widely by different inflammation of anterior and posterior segment of the eye and also in the postoperative management.